An insight of pathological anatomy of urethral stricture and surgical manipulations for children suffered from hypospadias - Yuanhong Xiao (BMC Urology, 2023)
Abstract Background Manipulation of urethral stricture is difficult and challenging. Accurate analysis and evaluation of the pathological circumstances of narrowed urethra and surrounding tissues were important for cure. The detailed descriptions of anatomic pathology of urethral stricture are rare. An insight of the pathological anatomy of the strictured urethra and the corresponding corrections is essential for an ultimate cure. The aim of the study is to interpret the pathological anatomies of the strictured urethra and the corresponding surgical manipulations. Methods From April 2007 to April 2020, eight boys who suffered from postoperative urethral stricture for hypospadias correction were studied retrospectively. The pathological anatomies of the strictured urethra were described and the corresponding surgical manipulations were analyzed. Results All eight patients were eventually cured through surgery. The patient age was 2.58–11 years old (mean value of 4.73). The therapeutic duration was 12–130 months (mean value of 47.75). The surgical manipulation was 1–9 times (mean value of 4.5). Curative follow-up was 8–138 months (mean value of 77.75). They were all applied with flap tubularization for their primary urethroplasty. Conclusions Based on the principal contradiction of the pathological anatomies of the urethral stricture, one-stage or staged surgical manipulations can be applied. After stricture was resolved, refining techniques of Mathieu, TIP, modified Duckett, glanular reconstruction and et al. can be used. Although it was tiring, utilizing the ventral or dorsal penile flap with relatively good blood supply and flexibility to reconstruct the urethra is possible and successful. To reconstruct an anatomically normal urethral tract should be pursued in the primary and consequential procedures for hypospadias and urethral stricture.